PREHISTORIC AND ROMAN GULLYING IN THE EUROPEAN LOESS BELT: A CASE STUDY FROM CENTRAL BELGIUM - Vanwalleghem T.; Poesen J.; Bork H.R.; Dotterweich M.; Schmidtchen G.; Deckers J.; Scheers S.; Martens M. (My University, 2006)
In contrast with the understanding of present-day soil erosion processes, knowledge on past soil erosion phenomena is still rather limited. Although some studies report on severe gully erosion phases during the fourteenth and eighteenth centuries, almost no evidence is available that documents earlier gully erosion phases. This study investigates the development and age of two old, permanent gullies that are conserved in the ancient Meerdaal forest in central Belgium. The development history of both gullies is very similar. In the first gully, archaeological evidence was found indicating an erosion phase during Roman times, followed by a partial infilling of the gully. In the second gully, radiocarbon dating provided evidence of the same Roman activity phase (cal. yr 46 BC-AD 78), but also of an earlier incision phase during the Middle Bronze Age (cal. yr 1743-1602, 1568-1533 BC). Also here, the erosion phase was followed by a partial infilling. This limited infilling indicates that the catchment of the gullies was reforested quite rapidly, hereby cutting off all runoff and sediment production. This has led to a unique situation in the Meerdaal forest, with the conservation of about 43 similar, large gullies in an area of about 17 km2. This area has a high geovalue, as the studied gullies are among the oldest and best conserved gullies in northwestern Europe. © 2006 Edward Arnold (Publishers) Ltd.
Keywords: ANCIENT FOREST; BELGIAN LOESS BELT; GULLY EROSION; LAND USE; LANDSCAPE EVOLUTION; PREHISTORIC; ROMAN